1981
DOI: 10.1159/000173337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nifedipine, Acebutolol, and Their Association on Exercise Tolerance in Patients with Effort Angina

Abstract: The action of nifedipine (N), acebutolol (A), and their association (A+N) was studied in 16 patients suffering from effort angina with documented coronary artery disease. The therapeutic action was valued by bicycle effort stress test after oral administration of medications in comparison with placebo (P), following a double-blind random sequence of treatments. Working capacity significantly increased after A (507 ± 450 mkp, p < 0.05), after N (1,140 ± 767 mkp, p < 0.001), and after A+N (1,198 ± 644 mkp, p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…However, some investigators have found significant improvement in exercise tolerance after nifedipine despite higher heart rate and blood pressure at peak exercise. 20 Moreover, a significant reduction in exercise- induced ST segment depression was observed after intracoronary administration of 0.1 mg of nifedipine, a dose that did not induce peripheral hemodynamic effects. '°In our study the peak-exercise double product was significantly higher after nifedipine in the seven patients in whom the drug improved exercise capacity, suggesting that the mechanism by which nifedipine exerted its salutary action was not secondary to a reduction in myocardial oxygen consumption.…”
Section: Discussionmentioning
confidence: 95%
“…However, some investigators have found significant improvement in exercise tolerance after nifedipine despite higher heart rate and blood pressure at peak exercise. 20 Moreover, a significant reduction in exercise- induced ST segment depression was observed after intracoronary administration of 0.1 mg of nifedipine, a dose that did not induce peripheral hemodynamic effects. '°In our study the peak-exercise double product was significantly higher after nifedipine in the seven patients in whom the drug improved exercise capacity, suggesting that the mechanism by which nifedipine exerted its salutary action was not secondary to a reduction in myocardial oxygen consumption.…”
Section: Discussionmentioning
confidence: 95%
“…The Italian group headed by DePonti [71] found mixed results in their study of diltiazem and acebutolol or propranolol. Patients exercised longer when given the combination, but more patients on the combination stopped exercising earlier because of fatigue, as compared to patients taking either of the single drugs.…”
Section: Chronic Stable Anginamentioning
confidence: 99%